A case of ileal enterolith secondary to eosinophilic enteritic stricture causing small bowel obstruction: a rare case report - Winford, Manna Elizabeth; Bhosle, Datta; Momin, Yasmin Altaf (International Surgery Journal, 2024)
Eosinophilic enteritis is an underdiagnosed and a rare inflammatory disease, that selectively affects the gastrointestinal tract with eosinophil rich inflammation in the absence of any known causes for eosinophilia. Enteroliths refer to stones formed in bowel due to severe stool stasis. They form around a nidus in layers which may contain calcification visible on radiographs. Here we present a case of a 65-year-old male with previous history of tuberculosis, who presented with transient small bowel obstruction with a large enterolith in distal ileum. He underwent exploratory laparotomy and was found to have an ileal stricture, secondary to eosinophilic enteritis. The post operative period was uneventful, and the patient was discharged on post operative day 8. Eosinophilic enteritis involves all layers of bowel wall and hence present with a wide range of symptoms from dyspepsia to bowel perforation. Stricture formation causing small bowel obstruction secondary to eosinophilic enteritis is rare. In this case report, stricture leads to stasis and formation of a fecolith, leading to small bowel obstruction. Eosinophilic enteritis needs to be considered as an important differential diagnosis for small bowel obstruction and small bowel strictures. In developing countries, as incidence of tuberculosis is high, it is common to wrongly diagnose a case of eosinophilic enteritis as tuberculosis. Thus, a strong clinical suspicion and awareness of this clinical entity are essential among surgical fraternity.